Syringic acid: structural elucidation and co-crystallization - Thipparaboina, Rajesh; Mittapalli, Sudhir; Thatikonda, Sowjanya; Nangia, Ashwini; Naidu, V. G. M.; Shastri, Nalini R. (Crystal Growth & Design, 2016)
Syringic acid (SYRA) is a potential antioxidant used in traditional Chinese medicine and is an emerging nutraceutical. Current reports claim its potential anti-angiogenic, anti-glycating, anti-hyperglycaemic, neuroprotective, and memory-enhancing properties in various animal models. To date, SYRA crystal structure has not been elucidated, and no crystal engineering studies have been reported. This study reports the crystal structure of SYRA for the first time along with its nicotinamide (SNCT-E) and urea (SU-EA-M) co-crystals. All forms were successfully characterized using single crystal X-ray diffraction (XRD), powder XRD, and differential scanning calorimetry. Single crystal analysis revealed that SYRA crystallized in the C2/c space group, whereas SNCT-E (2:1) and SU-EA-M (1:2) crystallized in the P21/n and Cmca space group, respectively. Novel co-crystals have shown improved solubility, modified dissolution profiles, and improved flow and compressibility. Cytotoxic effects were explored in DU145 prostate cancer cell lines for the first time, and significant enhancement in cytotoxicity by the co-crystals was observed compared to plain components. A two-fold increase in % cytotoxicity of SNCT-E was observed when compared to the corresponding physical mixture. These studies shed light on potential utility of SYRA as a coformer for various pharmaceutical applications to design synergistic and organ-protective co-crystals.